2012
DOI: 10.1590/s0004-27302012000900007
|View full text |Cite
|
Sign up to set email alerts
|

Densidade energética da dieta e fatores associados: como está a população de São Paulo?

Abstract: RESUMOObjetivo: Avaliar a densidade energética da dieta de adultos do município de São Paulo e fatores associados. Sujeitos e métodos: Participantes do estudo ISA-Capital, com amostragem probabilística (n = 710 adultos). O consumo alimentar foi avaliado pelo R24h. As correlações foram investigadas pelo coeficiente de correlação de Pearson. As associações com dados demográficos, socioeconômicos e de estilo de vida foram investigadas por modelos de regressão multivariados. Resultados: A densidade energética médi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
0
2
1
Order By: Relevance
“…The average energy density of the menu (lunch) observed in this study was 1.15 kcal/g, lower than the average observed for CRs in Brazil (1.34 kcal/g) [22]. The average observed in this study is even lower than the values observed in other studies that varied from 1.25 kcal/g [40] to 1.98 kcal/g [41]. High values of energy density are related to the poor quality of the diet, which can contribute to the increase of excess weight [41].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The average energy density of the menu (lunch) observed in this study was 1.15 kcal/g, lower than the average observed for CRs in Brazil (1.34 kcal/g) [22]. The average observed in this study is even lower than the values observed in other studies that varied from 1.25 kcal/g [40] to 1.98 kcal/g [41]. High values of energy density are related to the poor quality of the diet, which can contribute to the increase of excess weight [41].…”
Section: Discussioncontrasting
confidence: 87%
“…The average observed in this study is even lower than the values observed in other studies that varied from 1.25 kcal/g [ 40 ] to 1.98 kcal/g [ 41 ]. High values of energy density are related to the poor quality of the diet, which can contribute to the increase of excess weight [ 41 ]. Considering such evidence, national and international organizations recommend avoiding high-energy-density foods or meals concentrated in few meals [ 14 , 42 ].…”
Section: Discussioncontrasting
confidence: 86%
“…A ascensão do sobrepeso e da obesidade está associada com as mudanças nos padrões alimentares: aumento do consumo de gorduras, excesso de açúcar, e consumo insuficiente de frutas e hortaliças, levando a um aumento da densidade energética das dietas (Gorgulho et al, 2013;Marchioni et al, 2012;Bigio et al, 2011 (Colucci et al, 2011), e esteve associado ao elevado consumo de refrigerantes, sucos industrializados, achocolatado em pó e biscoitos recheados (Bueno et al, 2012). Em contrapartida, na mesma população, a ingestão diária de frutas, legumes e verduras mostra-se abaixo dos níveis recomendados pelo Ministério da Saúde (400g) para mais de 90% da população (Bigio et al, 2011).…”
Section: Padrão Alimentarunclassified